Contributions of the Process of Evidence-Based Practice to Implementation: Educational Opportunities. (1st May 2018) - Gambrill, Eileen
ABSTRACT: Values, knowledge, and skills integral to the process of evidence-based practice have much to offer efforts to implement evidence-based practices including recognizing ignorance as well as knowledge and identifying the need for deviations from mandated programs because of individual variations in client circumstances and differences, including cultural differences. Other contributions include highlighting the importance of creating cultures of inquiry in which participants are encouraged to use active open-minded thinking to critically appraise claims, gathering and collating vital questions that arise, involving clients as informed participants, and increasing transparency of what is done to what effect.